Food Sovereignty in Latin America: a gendered and multiescalar perspective (Alternautas, 2022)
This article aims to analyze how the concept of food sovereignty in Latin America has been constructed as a political tool for peasant women. In addition, it examines the practices found in this everyday life construction, by drawing on a multiscale perspective stemming from feminist political geography. With regard to peasant women, or rather, transnational networks of peasant women, it is necessary to take into account where their demands come from and how they lead women in one region to create networks with other women movements in the world in order to achieve their goals. In Latin America, the life of rural women in agriculture revolves around family care and food production at the local scale, and also at the regional scale. Women experience different forms of violence (by state, transnational companies, partners, etc.), and their consequences are perceived in everyday life. What occurs at the local scale is reflected in other scales, such as the state, the region, and the global. Peasant women are capable of recognizing their demands as women, particularly as peasant woman, which allows them to identify a point of convergence with women from different places in Latin America, sharing demands within the region since scales are mutually constitutive.